Normal and variant origin and branching pattern of inferior phrenic arteries and their clinical implications: a cadaveric study - Thamke, Swati; Rani, Pooja (International Journal of Research in Medical Sciences, 2017)
Background:Inferior phrenic arteries, which constitute the chief arterial supply to the diaphragm, are generally the branches of abdominal aorta, however, variations in their mode of origin is not uncommon. Very less information is available regarding the functional anatomy of the inferior phrenic artery in anatomy textbooks. Methods:The present study was conducted utilizing 36 formaline-fixed cadavers between 22 years to 80 years over a period of 5 years. The frequency and anatomical pattern of the origin of the right and left inferior phrenic arteries were studied. Results:On the right side, the inferior phrenic artery arose independently from abdominal aorta in 94.4% cases and on the left side in 97.2% cases.Other sources of origin were seen in 5.55% cases. Left hepatic artery was seen as the source of origin for right inferior phrenic artery in one case while in second case left gastric artery was the source for both the right and left inferior phrenic artery. The right inferior phrenic artery is the most common source of collateral arterial supply to hepatocellular carcinoma, next to the hepatic artery. Conclusion:Knowledge of variations of inferior phrenic artery origin could be valuable during treatment of hepatic neoplasm, liver transplants, biliary tract surgery and during tanscatheter oily chemoembolisation technique.